Cooperativas de crédito e formação da taxa de juros nas operações bancárias: teoria e evidências empíricas para o Brasil - Lhacer, Priscilla Maria Villa (2012)
This work aims to study whether credit unions can influence loan and deposit interest rates charged by Brazilian commercial banks. We based our research on Monti-Klein model for banks, Smith model for credit unions and the theory of Fama and Jensen about agency problems in the banking system. Therefore, we develop a theoretical framework to analyze the interaction between commercial banks and credit unions in credit and deposits markets. The empirical tests showed that credit unions influence banking interest rates through their market share. Higher credit union´s market share is associated to higher bank interest rates in credit operations. No evidence of impact of credit union´s market share in bank interest rates to deposits was found.